Pesan Dakwah K.H Zulkifli Muhammad Ali dalam Ceramah di Youtube pada Akun UZMA Media TV Channel - Siti Rohimah; Saripuddin (Islamic Journalism Department/ Program Studi Jurnalistik Islam, 2022)
This study used the library research method (literature research) which is explorative descriptive qualitative in nature. Qualitative research is concerned with non-numeric data, collecting and analyzing narrative data. Conducted on the YouTube channel